Female Resistance in the Bida’ah Film: A Critical Reflection on Patriarchal Culture and Religious Understanding - Tsania Mishbahun Naila; Primi Rohimi (Journal of Communication Studies, 2025)
The film Bida'ah is a Malaysian series that critically depicts female characters' resistance to injustice in the context of religion and patriarchal culture. A study of the film Bida'ah was conducted to provide an understanding of how visual media such as films can position women as subjects who have a voice, choices, and the courage to fight injustice. The problem statement in this study is how female characters in the film reflect resistance to patriarchal culture and religious understanding. This study aims to uncover the representation of female characters in the film Bida'ah as a form of criticism of patriarchal culture and religious understanding that limits women's roles. This study uses a qualitative approach with Roland Barthes' semiotic analysis method with three stages of analysis, namely denotation, connotation, and myth. The findings from this analysis are expected to make a significant contribution to the fields of patriarchy, cinema, and media studies in general. Patriarchal culture exploits this heresy as a tool to maintain power and social control over women, often disguised under the pretext of religious preaching and obedience. Thus, this study is not only a reflection on the courage of female characters in films, but also a call to strengthen the position of women in the public sphere and reinforce narratives of anti-patriarchal social change and gender equality.